An overview of early Malaysian settlement in relation to education - Yaman, Maheran (Common Ground, 2007)
In the context of Malaysia’s demographic heritage from pre-colonial, colonial and post-colonial periods, this research demonstrates the importance of Islamic beliefs to Malaysian educational philosophy. The description is based on official policy documents. The influence of colonials Western pedagogies on education are described.